Label-free multi-photon imaging using a compact femtosecond fiber laser mode-locked by carbon nanotube saturable absorber - Kieu, K. (Optical Society of America, 2013)
We demonstrate label-free multi-photon imaging of biological samples using a compact Er(3+)-doped femtosecond fiber laser mode-locked by a single-walled carbon nanotube (CNT). These compact and low cost lasers have been developed by various groups but they have not been exploited for multiphoton microscopy. Here, it is shown that various multiphoton imaging modalities (e.g. second harmonic generation (SHG), third harmonic generation (THG), two-photon excitation fluorescence (TPEF), and three-photon excitation fluorescence (3PEF)) can be effectively performed on various biological samples using a compact handheld CNT mode-locked femtosecond fiber laser operating in the telecommunication window near 1560nm. We also show for the first time that chlorophyll fluorescence in plant leaves and diatoms can be observed using 1560nm laser excitation via three-photon absorption.